2007
DOI: 10.1007/s00213-007-0708-0
|View full text |Cite
|
Sign up to set email alerts
|

Repeated phencyclidine in monkeys results in loss of parvalbumin-containing axo-axonic projections in the prefrontal cortex

Abstract: These results indicate that repeated treatment with phencyclidine results in plastic changes in parvalbumin-containing local circuit neurons in the prefrontal cortex similar to that reported in schizophrenia and that these changes may contribute to the common cognitive disruption seen in both schizophrenic patients and the phencyclidine monkey model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…We subsequently incubated the sections overnight with normal donkey serum (5:100), NaN3, and Triton X-100 and the primary antibodies. We used antibody 235 (1:2000; Swant) to recognize PV-IR cells, CB 38 (1:2000; Swant) for CB-IR cells, and AB5054 (1:2000; Merck Millipore, Millipore Bioscience Research Reagents) for CR-IR cells (Morrow et al, 2007;Mascagni et al, 2009;Tricoire et al, 2011). For the AMPAR subunits, we used AB1504 (1:100; Merck Millipore, Millipore Bioscience Research Reagents) for GluA1 (Wenthold et al, 1996;Betarbet and Greenamyre, 1999) (Martin et al, 1993;Carder, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…We subsequently incubated the sections overnight with normal donkey serum (5:100), NaN3, and Triton X-100 and the primary antibodies. We used antibody 235 (1:2000; Swant) to recognize PV-IR cells, CB 38 (1:2000; Swant) for CB-IR cells, and AB5054 (1:2000; Merck Millipore, Millipore Bioscience Research Reagents) for CR-IR cells (Morrow et al, 2007;Mascagni et al, 2009;Tricoire et al, 2011). For the AMPAR subunits, we used AB1504 (1:100; Merck Millipore, Millipore Bioscience Research Reagents) for GluA1 (Wenthold et al, 1996;Betarbet and Greenamyre, 1999) (Martin et al, 1993;Carder, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the effect of acute intake, chronic ketamine intake has been shown to result in a reduction in the number of parvalbumin-containing axoaxonic cartridges (see Fig 4). These are synaptic terminals of inhibitory chandelier cells [149]. The reduced input on parvalbumin-containing interneurons (indicating low pyramidal activity) have been suggested to not only reduce parvalbumin, but to also downregulate GAD67, the principal synthesizing enzyme for GABA [149,246].…”
Section: Nmdamentioning
confidence: 99%
“…Furthermore, while the behavioral and neurochemical effects of acute exposures to NMDA-R antagonists are believed to occur upon disinhibition of cortical excitatory activity due to increased sensitivity of inhibitory systems to blockade of NMDA-R function (Olney et al, 1999;Homayoun and Moghaddam, 2007;Lisman et al, 2008;Middleton et al, 2008), they do not lead to the enduring changes in PV-interneurons observed in schizophrenia. Repetitive exposures to NMDA-R antagonists, on the other hand, produce a reduction in GAD67 expression in PVinterneurons of rodents (Behrens et al, 2007 as well as decreased expression of parvalbumin in rodents and non-human primates (Cochran et al, 2002;Keilhoff et al, 2004;Rujescu et al, 2006;Morrow et al, 2007).…”
Section: Introductionmentioning
confidence: 99%